2011
DOI: 10.1002/hep.24185
|View full text |Cite
|
Sign up to set email alerts
|

“Real-Life” comparison of pegylated-interferon 2a versus 2b combination therapy of chronic hepatitis C virus

Abstract: We read with great interest the article by Stepanova et al. 1 In this report from the United States with 10,582 eligible individuals (1.52% of whom were positive for hepatitis C virus [HCV] antibody [anti-HCV]), the rate of insurance coverage was significantly lower in patients with HCV infection (61.2%), particularly in 66.7% patients who could be candidates for treatment (54.3%), than in subjects without HCV infection (81.2%). Only 36.3% of HCV-infected patients were potentially eligible for treatment and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…We observed an overall SVR rate of 50% for all genotypes in group A, which is comparable to SVR rates found in randomized clinical trials of peg-INF and ribavirin in HCV/HIV co-infected patients (27% to 40%) [11,12,28]. However, the SVR rates in mono-infected patients (52%) are slightly lower than those reported by a real-life cohort study of mono-infected patients treated by gastroenterologists at the same institution in the same time span (60,9%) [7]. The reasons for these differences are not clear, but we have to keep in mind that the ID clinic is attending for international patients, who might have different IL-28 haplotypes [7].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…We observed an overall SVR rate of 50% for all genotypes in group A, which is comparable to SVR rates found in randomized clinical trials of peg-INF and ribavirin in HCV/HIV co-infected patients (27% to 40%) [11,12,28]. However, the SVR rates in mono-infected patients (52%) are slightly lower than those reported by a real-life cohort study of mono-infected patients treated by gastroenterologists at the same institution in the same time span (60,9%) [7]. The reasons for these differences are not clear, but we have to keep in mind that the ID clinic is attending for international patients, who might have different IL-28 haplotypes [7].…”
Section: Discussionsupporting
confidence: 63%
“…However, the SVR rates in mono-infected patients (52%) are slightly lower than those reported by a real-life cohort study of mono-infected patients treated by gastroenterologists at the same institution in the same time span (60,9%) [7]. The reasons for these differences are not clear, but we have to keep in mind that the ID clinic is attending for international patients, who might have different IL-28 haplotypes [7]. Also, it has to be noted that 9/84 of the mono-infected patients were lost to follow-up.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The IDEAL study by McHutchison et al reported similar SVR rates of 40.9% (95% confidence interval [CI], 37.9-43.9) with peginterferon alfa-2a and 39.8% (95% CI, 36.8-42.8) with peginterferon alfa-2b (p = 0.57) [8]. In 2011, Zurwiesch et al studied a German cohort of 486 patients and reported no significant difference in the SVR rates with peginterferon alfa-2a (53.4%) and alfa-2b (53.7%) [11]. However, some authors have reported better responses with peginterferon alfa-2a.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials provide a high level of medical and supportive care, which tends to maximize patient compliance, and the inclusion and exclusion criteria may not reflect the clinical picture in a real-life setting [11]. Thus, the main objective of this study was to conduct a "reallife" comparison of peginterferon alfa-2a versus alfa2b plus ribavirin in a Mexican population with HCV genotype 1.…”
Section: Introductionmentioning
confidence: 99%